'If we had more like her we would no longer be the unheard majority': Germaine Greer's reception in the United States. Issue 87 (2nd January 2016) - Sheehan, Rebecca J.
ABSTRACT: This article examines Germaine Greer's reception in the United States in 1971, the year that The Female Eunuch was first published there. Using hundreds of previously unexamined letters sent by television viewers after she hosted The Dick Cavett Show, the article explores the impact of Greer's media engagement and the overwhelmingly positive reception she received from this particular audience. The letters detail Greer's strength, intelligence, wit, and keen ability to communicate. They demonstrate that she educated many audience members about feminist issues including abortion and rape, and inspired pride in her female audience. The sympathetic portrait of Greer in these letters contrasts with the more polarised view of Greer in the print media responses to her: the mainstream print media portrayed and embraced Greer as its ideal non-threatening, attractive and heterosexual feminist, and American feminists dismissed her as an opportunist. Taken together, the unpublished audience letters and the print media sources provide a more complex portrait of Greer's reception and effectiveness. The letters speak for Greer and – now that they are available in Greer's carefully preserved personal archive – restore the voices of the ordinary people who helped to shape the history of feminism.